2020
DOI: 10.46328/ijtes.v4i3.105
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduates’ Attitude towards the Utilization of Open Educational Resources for Learning

Abstract: This study investigated Undergraduates’ Attitude towards the utilization of OER among Undergraduates and the influence of gender and area of specialization on their attitude towards the use. The study adopted a descriptive method of the quantitative research. 3 research questions were developed and answered. 398 respondents were randomly sampled from 3 purposively selected area of specializations. Frequency counts, percentage, rank order and mean were used to answer research questions 1 to 3. The findings of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 8 publications
2
6
0
Order By: Relevance
“…vocational and technical education lecturers towards utilizing open educational resources (OER) for effective teaching and learning in Nigerian universities include Designing and implementing training programs specifically focused on OER utilization, Establishing centralized repositories of high-quality OER materials tailored to vocational and technical education, and Encourage collaboration among vocational and technical education lecturers. The findings are in tandem withIssa, et al (2020) andOnaifo (2016) who reported that if the universities in Nigeria will collaborate and operate a central library that will be managed by the National University Commission (NUC) where information will be stored and retrieved without restrictions will enhance the utilization of OERs among lecturers in the universities and the individual university OERs and not reliable due to poor maintenance from the institutions. In the same vein,Zaid and Alabi (2021) and Loveline (2022) suggested that Advocating for institutional policies and funding support for OER initiatives are imperatives for the effective utilization of OERs in teaching and learning.…”
supporting
confidence: 65%
“…vocational and technical education lecturers towards utilizing open educational resources (OER) for effective teaching and learning in Nigerian universities include Designing and implementing training programs specifically focused on OER utilization, Establishing centralized repositories of high-quality OER materials tailored to vocational and technical education, and Encourage collaboration among vocational and technical education lecturers. The findings are in tandem withIssa, et al (2020) andOnaifo (2016) who reported that if the universities in Nigeria will collaborate and operate a central library that will be managed by the National University Commission (NUC) where information will be stored and retrieved without restrictions will enhance the utilization of OERs among lecturers in the universities and the individual university OERs and not reliable due to poor maintenance from the institutions. In the same vein,Zaid and Alabi (2021) and Loveline (2022) suggested that Advocating for institutional policies and funding support for OER initiatives are imperatives for the effective utilization of OERs in teaching and learning.…”
supporting
confidence: 65%
“…As a consequence, students' attitudes towards and experiences with OER have only been researched to a very limited extent (Axe et al, 2020;Hilton et al, 2020). Students have been shown to have, for the most part, a positive attitude towards using OER; likely motivators for student engagement with OER encompass assessment requirements, learner awareness and involvement, engagement with communities of practice, and lecturers' attitudes (Issa et al, 2020;Jurado & Pettersson, 2020).…”
Section: Attitudes Towards Open Educationmentioning
confidence: 99%
“…Issa et al 12 conducted a research study to investigate the undergraduates' attitude towards the utilisation of open educational resources. Out of 6 universities in Kwara state (Nigeria), the researcher selected three universities and three major subject disciplines.…”
Section: Literature Reviewmentioning
confidence: 99%